Innovation aspects of Slovenian manufacturing companies and their managers - Palčič, Iztok; Kocijančič, Tomaž; Bale, Norma (Anali PAZU HD, 2022)
This paper deals with several aspects of innovation in Slovenian manufacturing companies. The authors present the results of their research from 2013. The first part of the paper deals with the use of organisational innovation concepts. The authors present the concept of organisational innovation and its meaning. Later they present the frequency use of selected organisational concepts in Slovenian manufacturing companies. The paper also presents the impact of these concepts on companies’ innovation and performance level. The second part of the paper deals with the managers of manufacturing companies and their attitude towards innovation. The key finding is that the manufacturing companies are aware of the importance of innovation processes, while managers’ innovation profile shows that managers actively cooperate in innovation process, but are reluctant to creativity fostering and open innovation.
Keywords: innovation; organisational innovation; innovation profile; manufacturing company